The Development of Learning Tools Through Question Student Have (QSH) Method in Tarikh Education to Improve Students’ Self-Confidence - Raniya, Pudyas Tataquna; Susanto, Shobri Firman; Arqam, Mhd Lailan; Perawironegoro, Djamaluddin (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aims to improve students' active learning activities through the application of the question student have method that has been developed in learning tarikh at SMP Muhammadiyah 1 Gamping. This method is designed to train students in the ability to ask questions, so that they are not only passive listeners, but also active in reading, writing, and discussing. This study used the research and development method with quantitative and qualitative approaches. The results showed that the application of the QSH method can increase students' self-confidence and motivation, with 89% of respondents assessing the products produced as “Very Good” quality and the influence on the self-confidence variable through the pretest post-test which showed 65,64 increased to 89,18. These findings are expected to make a positive contribution to the development of more interactive and effective learning methods in Islamic education.